Comparative Study of Capillary Filtration Coefficient (Kfc) Determination by a Manual and Automatic Perfusion System. Step by Step Technique Review - Bravo-Reyna, C C; Torres-Villalobos, G; Aguilar-Blas, N; Frías-Guillén, J; Guerra-Mora, J R (Physiological research, 2019)
The purpose of calculating the capillary filtration coefficient is to experimentally evaluate edema formation in models of pulmonary ischemia-reperfusion injury. For many years, the obtaining of this coefficient implies a series of manual maneuvers during ex-vivo reperfusion of pulmonary arterial pressure, venous pressure and weight, as well as the calculation of the Kfc formula. Through automation, the calculation of capillary filtration coefficient could be easier and more efficient. To describe an automatic method designed in our laboratory to calculating the capillary filtration coefficient and compare with traditional determination of capillary filtration coefficient as gold standard method. An automatic three valve perfusion system was constructed, commanded by a mastery module connected to a graphical user interface. To test its accuracy, cardiopulmonary blocks of Wistar rats were harvested and distributed in manual (n=8) and automated (n=8) capillary filtration coefficient determination groups. Physiological parameters as pulmonary arterial pressure, pulmonary venous pressure, weight and capillary filtration coefficient were obtained. Results: Capillary filtration coefficient, pulmonary arterial pressure, venous arterial pressure shown no statistical significance difference between the groups. The automated perfusion system for obtaining Kfc was standardized and validated, giving reliable results without biases and making the process more efficient in terms of time and personal staff.
Keywords: Capillaries; kapilární permeabilita; venae pulmonales; plicní tlak v zaklínění; Organ Culture Techniques; orgánové kultury - kultivační techniky; krysa rodu Rattus; zvířata; Capillary Permeability; potkani Wistar; Perfusion; Rats, Wistar; perfuze; Pulmonary Veins; Rats; Animals; arteria pulmonalis; Pulmonary Wedge Pressure; kapiláry; Pulmonary Artery